Study of the Effect of Spark Advance, Engine Speed Variation and Number of Spark Plugs on Engine Performance Using CFD Software - Akhil R, Joshi; Sachin L, Borse (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
CFD Models have been extensively validated and used to predict the performance and emissions of spark ignition (SI) engines and compression ignition CI engines. As opposed to experimental methods, numerical methods are often less expensive and faster. The present work is the numerical investigation of spark ignition SI engines using open-source Computational Fluid Dynamics (CFD) tool OpenFOAM. The effect of spark advance, engine speed variation and number of spark plugs on engine performance is studied with OpenFOAM module engineFOAM. The standard k-e turbulence model is used along with Reynolds Averaged Navier Stokes (RANS) equations for simulating flow field and heat transfer. The cylinder geometry is created in ICEM CFD and converted to Open FOAM. The variation in pressure and temperature values in the cylinder with crank angle are plotted. Also contours for temperature distribution and reaction regress variable are plotted.